MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS XI.3 PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI PENGGUNAAN MEDIA GOOGLE SITES DI SMA NEGERI 3 PALEMBANG - Sri Ade Kayanti; Umi Chotimah; Tyas Masito Mutiara; Putri Amelia Muharram Zu; Ria Amanda; Rana Karimah; Wulan Triyuni Damayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The learning of Pancasila education is often considered uninteresting due to the less challenging material and the less engaging teaching methods and media. However, it is urgent to shape the character of students who possess morals and love for their homeland. This research aims to describe and explain how using Google Sites websites as a learning medium can foster students' interest in studying Pancasila Education in class XI.3 at SMA Negeri 3 Palembang. In this study, the methods used were observation, questionnaires, and tests. The results indicate that the students of class XI.3 at SMA Negeri 3 Palembang are facing issues in the learning of Pancasila education, specifically that the students need higher concentration and also need more interest in studying. The solution used by the researchers to address this issue is conducting experiments using Google Sites as a medium in the learning process. Using that media has been proven to enhance student's learning motivation, as evidenced by observations of students' attitudes during lessons and the results of questionnaires given to students after the Pancasila Education class in the Merdeka Curriculum.